Analisis Kualitas Pelayanan Sistem Informasi dan Budaya Lapor di Lingkungan Ombudsman RI Dengan Metode SERVQUAL - Farchan Monoarfa, Mahardhika (Jurnal Nasional Teknologi Komputer, 2022)
The rapid internet technological development makes web-based services develop rapidly. Web-based services are very useful in accelerating the supervision of public services. The Ombudsman of the Republic of Indonesia (ORI) is a state institution that has the authority to oversee the implementation of public services. However, many people still report on media instead of using the Ombudsman RI website. The purpose of this study is to analyze the service quality of reporting system on the Ombudsman information systems web. The quality measurement method uses the Service Quality (SERVQUAL) method that consists of five dimensions of service quality modified, usability, information quality, services reliability, assurance, and empathy. The research instrument uses primary data through the questionnaires and is processed quantitatively. The results showed a negative gap between expectations and perceptions in measuring the quality of the information system of Ombudsman RI. It shows that the web information system has not met the expectations of its users yet. So it can affect the culture of public reporting through the Ombudsman RI website.